2020
DOI: 10.1002/jlb.4ma0420-568r
|View full text |Cite
|
Sign up to set email alerts
|

IL-18R signaling is required for γδ T cell response and confers resistance to Trypanosoma cruzi infection

Abstract: IFN-producing T cells have been suggested to play an important role in protection against infection with Trypanosoma cruzi. However, little is known about the mechanisms leading to functional differentiation of this T cell subset in this model. In the current work, we investigated the possibility that the IL-18/MyD88 pathway is central for the generation of effector T cells, playing a role for resistance against infection. We found that splenic + CD3 + cells were rapidly expanded (10-14 days post infection), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…It has been shown that CD27 + IFNγ-prone γδ T cells expand substantially more than CD27 − IL-17-biased γδ T cells upon adoptive transfer; and the stimulation via the TCR greatly favors IFNγ over IL-17A producers 71,72 ). Previously, γδ T cell transfer was shown to be capable of controlling Trypanosoma infection seemingly through IFN-γ-producing γδ T cells 73 . A similar protection is observed in Toxoplasma infection 74 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CD27 + IFNγ-prone γδ T cells expand substantially more than CD27 − IL-17-biased γδ T cells upon adoptive transfer; and the stimulation via the TCR greatly favors IFNγ over IL-17A producers 71,72 ). Previously, γδ T cell transfer was shown to be capable of controlling Trypanosoma infection seemingly through IFN-γ-producing γδ T cells 73 . A similar protection is observed in Toxoplasma infection 74 .…”
Section: Discussionmentioning
confidence: 99%
“…gd T cells also express cytokine receptors, like IL-2Rbg, IL-18R, IL-7Ra, IL23R (107)(108)(109)(110)(111), which can deliver activated signals by binding to interleukins. Stimulation of these cytokine receptors can not only enhance the effect function of gd T cells, but also directly trigger the activation of gd T cells even in the absence of TCR signal.…”
Section: Other Receptors Delivering Signals In Gd T Cellsmentioning
confidence: 99%
“…Several molecules and pathways regulate CD27 + IFNγ-producing γδ T cells. Cytokines, including IL-2, IL-12, and IL-15, activate T-bet and EOMES transcription factors to drive expression of IFNγ in these cells (Barros-Martins et al, 2016 ; Chen et al, 2007 ; He et al, 2010 ; Lino et al, 2017 ; Yang et al, 2020 ; Yin et al, 2002 ; Yin et al, 2000 ), while IL-2, IL-15, and IL-18 stimulate their proliferation (Corpuz et al, 2016 ; da Mota et al, 2020 ; Ribot et al, 2012 ). Co-stimulation through CD27 and CD28 augments survival and mitogenic signals for these cells (Ribot et al, 2010 ; Ribot et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%